Algorithmic Personalization as a Mode of Individuation - Lury, Celia; Day, Sophie (Theory, culture & society, 2019)
Recognizing that many of the modern categories with which we think about people and their activities were put in place through the use of numbers, we ask how numbering practices compose contemporary sociality. Focusing on particular forms of algorithmic personalization, we describe a pathway of a-typical individuation in which repeated and recursive tracking is used to create partial orders in which individuals are always more and less than one. Algorithmic personalization describes a mode of numbering that involves forms of de- and re- aggregating, in which a variety of contexts are continually included and excluded. This pathway of a-typical individuation is important, we suggest, to a variety of domains and, more broadly, to an understanding of contemporary economies of sharing where the politics of collectivities, ownership and use are being reconfigured as a default social.